Introducing mathematics undergraduate students to the theorem prover lean - Garnelo Abellanas, Irene; Liebendörfer, Michael (Thirteenth Congress of the European Society for Research in Mathematics (CERME13))

Feynman–Kac Formula and Asymptotic Behavior of the Minimal Energy for the Relativistic Nelson Model in Two Spatial Dimensions - Hinrichs, Benjamin; Matte, Oliver (Annales Henri Poincaré)

Super-Gaussian decay of exponentials: A sufficient condition - Hinrichs, Benjamin; Janssen, Daan W.; Ziebell, Jobst (Journal of Mathematical Analysis and Applications)
Keywords: Applied Mathematics; Analysis

Assessment of the Physicochemical Meaning of the Ohmic Series Resistance Observed for High Frequencies in Electrochemical Impedance Spectra - Reinke, Sebastian; Khamitsevich, Vera; Röth, Oliver; Linnemann, Julia (2023 International Workshop on Impedance Spectroscopy (IWIS))
Attributing features of electrochemical impedance spectra to electrochemical phenomena is both crucial and frequently ambiguous. To elucidate the origin of the ohmic part of the spectrum, activated carbon electrodes were prepared with different contents of polyacrylic acid as binder. Their impedance spectra and cyclic voltammograms were recorded using sulfuric acid of five different concentrations as the electrolyte. To distinguish electrolyte resistance and resistances related to the activated carbon layer of the electrode, the specific electrolyte conductivity was independently measured and compared against the ohmic part of the electrochemical impedance spectra (EIS). The capacitive cyclic voltammograms show larger resistive contributions with higher scan rate and lower electrolyte conductivity. Comparing the ohmic part of the EIS to the specific resistance of the electrolyte, a linear function with no statistically significant offset was found. The ohmic part of the EIS, thus, reflects the electrolyte resistance, not that of the carbon electrode.
Keywords: electrochemical impedance spectroscopy; supercapacitors; carbon

Datengestützte Produktplanung
Unter dem Einfluss der Digitalisierung wandeln sich mechatronische Produkte zunehmend in cyber-physische Systeme (CPS). Diese sind in der Lage, umfangreiche Daten während ihres Betriebs zu sammeln und über digitale Netzinfrastrukturen zur Verfügung zu stellen. Gemeinsam mit weiteren Daten aus der Betriebsphase versprechen sie wertvolle Erkenntnisse über das Produkt und dessen Nutzer, welche für die Hersteller der CPS insbesondere für die Planung zukünftiger Produktgenerationenrelevant sind. Die zielgerichtete Nutzung von Betriebsdaten in der strategischen Produktplanung stellt produzierende Unternehmen jedoch noch vor zahlreiche Herausforderungen, z. B. hinsichtlich der Identifizierung Erfolg versprechender Use Cases. Das vorliegende Buch greift diese Herausforderungen auf und stellt ein Instrumentarium vor, das produzierende Unternehmen zur datengestützten Produktplanung befähigt. Neben der Vorstellung praxiserprobter Methoden und Werkzeuge werden Einblicke in vier Pilotprojekte gegeben. Das Instrumentarium entstand im Forschungsprojekt „DizRuPt“, das vom Bundesministerium für Bildung und Forschung (BMBF) gefördert wurde.

The Impact of a School Dog on Children’s Social Inclusion and Social Climate in Class - Mombeck, Mona Maria; Albers, Timm (European Journal of Investigation in Health, Psychology and Education)
Animal-assisted pedagogy is well known in classroom practice, but scientific evidence of its impact on teaching and learning conditions is still lacking. At the same time, the biggest challenge in education systems worldwide is the social inclusion of students. In a pre–post design, 30 heterogeneous students (16 f/14 m) from four different school classes (grades 5–8) of two secondary schools and one grammar school were interviewed (in a problem-centered interview) about their social inclusion and their social climate in class before and after being taught selected subjects with a school dog for one school term. At the second measurement point, participants were also asked about their perception of animal-assisted pedagogy. The qualitative data analysis (Kuckartz) showed that the presence of a dog leads to an improved social climate, more social integration and to a change in social roles; therefore, we discussed our findings in the context of role theory (Krappmann). In addition, we found that the mutual perception of the other students and the teacher changes to a more positive and friendlier image. Through animal-assisted pedagogy, a new social role is added to the classroom, where caring and bonding are prioritized. Social interaction and norms are influenced and stereotypical and individual roles can be changed. Therefore, animal-assisted pedagogy can be key to promoting social inclusion in the school environment.

Phase sensitivity of spatially broadband high-gain SU(1,1) interferometers - Scharwald, Dennis; Meier, Torsten; Sharapova, Polina (Physical Review Research)

Crossing Boundaries: Autoethnography of Subjective Experiences During Meditation - Kothe, Anna-Katharina; Vochatzer, Stefanie; Oesterle, Christian; Ruf, Steffen Philipp (The Qualitative Report)
In this autoethnographic quadrologue, the authors aim to show how meditation experiences defy verbalization in a qualitative research setting. This leads to the insight that an autoethnographic approach may be a much better fit for such an experience, where complex and inexpressible things can be found. This is especially the case since autoethnographic texts include and immerse the reader in the experience. Even though in the case of meditation this can hardly be achieved, this quadrologue aims at conveying some of the struggles and peculiarities of meditation practice. It focuses on the research process leading to the decision to employ an autoethnography paradigm. Thus, the focus of this article is the differentiation of autoethnography from other methodological approaches and the conscious decision in favour of this method, which is rather unusual in German-speaking countries. The authors develop the thesis that both the meditation experience and the decision to employ an autoethnographic paradigm led to the experience of “wandering off the beaten track” and crossing the boundaries of what is usually done in society and social science respectively.

Podcasts in der Hochschullehre: mittelalt & literarisch. - Elbwart, Katharina; Winter, Katja; Keidel, Matthias (Beackerte Felder: Kultur, Bildung, Erinnerung. Gaby Herchert zum 65. Perspektiven des Regionalen Band 1)

Beackerte Felder: Kultur, Bildung, Erinnerung. Gaby Herchert zum 65. Perspektiven des Regionalen

Developing language teacher identity and leadership skills in intercultural learning environments - Elbwart, Katharina; Keatinge, Dagmar (Language Teacher Leadership. Insights from Research and Practice.)

MAAS: Hiding Trojans in Approximate Circuits - Ahmed, Qazi Arbab; Awais, Muhammad; Platzner, Marco (2023 24th International Symposium on Quality Electronic Design (ISQED))

Talentsuche im paralympischen Sport (ParaTalent) - Radtke, Sabine; Vogel, Alina
Keywords: Para Sport; Talentmaßnahmen; Nachwuchs

The Consumerization of Care: How Capitalism Is Co-Opting Solidarity - Alberternst, B.; Giesler, M.; Steinhoff, Lena; Eggert, A.

Life Cycle Assessment of Lightweight Structures in Vehicles for New Mobility Concepts - Ostermann, Moritz; Dierkes, Eric; Marten, Thorsten; Tröster, Thomas (Proceedings of the 18th Conference on Sustainable Development of Energy, Water and Environmental Systems, Dubrovnik, Croatia 2023)

Electrochemical Sodium Storage in Hard Carbon Powder Electrodes Implemented in an Improved Cell Assembly: Insights from In-Situ and Ex-Situ Solid-State NMR - Šić, Edina; Schutjajew, Konstantin; Haagen, Ulrich; Breitzke, Hergen; Oschatz, Martin; Buntkowsky, Gerd; Gutmann, Torsten (Chemsuschem)
Abstract In this work, we report on an improved cell assembly of cylindrical electrochemical cells for 23Na in-situ solid-state NMR (ssNMR) investigations. The cell set-up is suitable for using powder electrode materials. Reproducibility of our cell assembly is analyzed by preparing two cells containing hard carbon (HC) powder as working electrode and sodium metal as reference electrode. Electrochemical storage properties of HC powder electrode derived from carbonization of sustainable cellulose are studied by ssNMR. 23Na in-situ ssNMR monitors the sodiation/desodiation of a Na{|}NaPF6{|}HC cell (cell 1) over a period of 22?days, showing high cell stability. After the galvanostatic process, the HC powder material is investigated by high resolution 23Na ex-situ MAS NMR. The formation of ionic sodium species in different chemical environments is obtained. Subsequently, a second Na{|}NaPF6{|}HC cell (cell 2) is sodiated for 11?days achieving a capacity of 220?mAh/g. 23Na ex-situ MAS NMR measurements of the HC powder material extracted from this cell clearly indicate the presence of quasi-metallic sodium species next to ionic sodium species. This observation of quasi-metallic sodium species is discussed in terms of the achieved capacity of the cell as well as of side reactions of sodium in this electrode material.
Keywords: solid-state nmr; hard carbon; electrochemical cells; in-situ characterization; sodium

SiCO Ceramics as Storage Materials for Alkali Metals/Ions: Insights on Structure Moieties from Solid-State NMR and DFT Calculations - Šić, Edina; Rohrer, Jochen; Ricohermoso, Emmanuel; Albe, Karsten; Ionescu, Emmanuel; Riedel, Ralf; Breitzke, Hergen; Gutmann, Torsten; Buntkowsky, Gerd (Chemsuschem)
Abstract Polymer-derived silicon oxycarbide ceramics (SiCO) have been considered as potential anode materials for lithium- and sodium-ion batteries. To understand their electrochemical storage behavior, detailed insights into structural sites present in SiCO are required. In this work, the study of local structures in SiCO ceramics containing different amounts of carbon is presented. 13C and 29Si solid-state MAS?NMR spectroscopy combined with DFT calculations, atomistic modeling, and EPR investigations, suggest significant changes in the local structures of SiCO ceramics even by small changes in the material composition. The provided findings on SiCO structures will contribute to the research field of polymer-derived ceramics, especially to understand electrochemical storage processes of alkali metal/ions such as Na/Na+ inside such networks in the future.
Keywords: NMR spectroscopy; Ceramics; defects; density functional calculations; EPR spectroscopy

Collaborative Mechanistic Effects between Vanadia and Titania during the Oxidative Dehydrogenation of Propane Investigated by Operando and Transient Spectroscopies - Schumacher, Leon; Pfeiffer, Johannes; Shen, Jun; Gutmann, Torsten; Breitzke, Hergen; Buntkowsky, Gerd; Hofmann, Kathrin; Hess, Christian (ACS Catalysis)
The oxidative dehydrogenation (ODH) of propane is of great technical importance, and supported VOx catalysts have shown promising properties for the reaction. One of the most prominent and active supports is titania, which exhibits a high activity but many questions regarding the catalyst system are still in debate. In this study, we elucidate the mechanism of the propane ODH reaction over VOx/TiO2, using P25 and ALD (atomic layer deposition) synthesized TiO2/SBA-15 as a support, with X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD), 51V solid-state (ss)NMR, operando multiwavelength Raman, operando UV–vis, and transient IR spectroscopies. Bare titania shows a small conversion, leading to carbon formation, and the reaction occurs at the interface between anatase and rutile. In comparison, in VOx/TiO2 catalysts, the activity shifts from titania to vanadia sites. UV-Raman spectroscopy and structural characterization data revealed the reaction to involve preferentially the V═O bonds of dimeric species rather than doubly bridged V–O–V bonds, which leads to higher propene selectivities. The active vanadium site shows a nuclearity-dependent behavior; that is, at higher loadings, when oligomeric vanadia is present, it shifts from V═O bonds to linear V–O–V bonds in oligomers, leading to less selective oxidation due to the better reducibility. Our operando/transient spectroscopic results demonstrate the direct participation of the titania support in the reaction by influencing the degree of vanadia oligomerization and enabling rapid hydrogen transfer from propane to vanadia via Ti–OH groups on anatase, accelerating the rate-determining step of the initial C–H bond breakage. The broader applicability of the results is confirmed by the behavior of the ALD-synthesized sample, which resembles that of P25. Our results highlight the detailed level of mechanistic understanding accessible from multiple spectroscopic approaches, which can be readily transferred to other materials and/or reactions. The oxidative dehydrogenation (ODH) of propane is of great technical importance, and supported VOx catalysts have shown promising properties for the reaction. One of the most prominent and active supports is titania, which exhibits a high activity but many questions regarding the catalyst system are still in debate. In this study, we elucidate the mechanism of the propane ODH reaction over VOx/TiO2, using P25 and ALD (atomic layer deposition) synthesized TiO2/SBA-15 as a support, with X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD), 51V solid-state (ss)NMR, operando multiwavelength Raman, operando UV–vis, and transient IR spectroscopies. Bare titania shows a small conversion, leading to carbon formation, and the reaction occurs at the interface between anatase and rutile. In comparison, in VOx/TiO2 catalysts, the activity shifts from titania to vanadia sites. UV-Raman spectroscopy and structural characterization data revealed the reaction to involve preferentially the V═O bonds of dimeric species rather than doubly bridged V–O–V bonds, which leads to higher propene selectivities. The active vanadium site shows a nuclearity-dependent behavior; that is, at higher loadings, when oligomeric vanadia is present, it shifts from V═O bonds to linear V–O–V bonds in oligomers, leading to less selective oxidation due to the better reducibility. Our operando/transient spectroscopic results demonstrate the direct participation of the titania support in the reaction by influencing the degree of vanadia oligomerization and enabling rapid hydrogen transfer from propane to vanadia via Ti–OH groups on anatase, accelerating the rate-determining step of the initial C–H bond breakage. The broader applicability of the results is confirmed by the behavior of the ALD-synthesized sample, which resembles that of P25. Our results highlight the detailed level of mechanistic understanding accessible from multiple spectroscopic approaches, which can be readily transferred to other materials and/or reactions.

Peptides as Model Systems for Biofunctionalizations of Cellulose─Synthesis and Structural Characterization by Advanced Solid-State Nuclear Magnetic Resonance Techniques - Limprasart, Waranya; Höfler, Mark Valentin; Kunzmann, Nico; Rösler, Lorenz; Herr, Kevin; Breitzke, Hergen; Gutmann, Torsten (The Journal of Physical Chemistry C)
The tailored design of bioactive materials based on cellulose or paper is still a challenging task. It requires detailed knowledge of the structure and interaction of the biofunctionalization with the carrier material at the nanoscale. In this work, the small peptide sequence Acetyl-Pro-Ala-Phe-Gly-OH (peptide 1) that can serve as a model for biofunctionalization is synthesized via solid-phase peptide synthesis, purified, and characterized by high-performance liquid chromatography (HPLC) and mass spectrometry (MS). The as-obtained peptide is bound to microcrystalline cellulose (MCC) via a wet chemical approach. Quantification of the peptide on the MCC carrier is performed by replacing l-proline (Pro) in the peptide sequence by 4-fluoro-l-proline (Pro(19F)) (peptide 2) and applying 19F magic angle spinning nuclear magnetic resonance (MAS NMR). Detailed characterization of the model system is provided by using 1H → 13C cross-polarization magic angle spinning (CP MAS NMR) combined with dynamic nuclear polarization (DNP) to enhance sensitivity. Analysis of the binding of the peptide on MCC necessitates the replacement of l-glycine (Gly) in the sequence by 13C-labeled l-glycine (Gly(13C)) (peptide 3). DNP-enhanced 13C–13C correlation experiments carried out with dipolar assisted rotational resonance (DARR) are then used to analyze the proximity between the model peptide and the MCC carrier. The strength of the dipolar coupling is estimated from the DNP-enhanced 1H → 13C CP MAS double-quantum rotational resonance (DQrotres) experiment. The obtained dipolar coupling between the 13C═O carbon of peptide 3 and the C6 carbon of the cellulose is equal to a carbon–carbon distance of about two C–O bond lengths, which strongly suggests the binding of significant amounts of the peptide on MCC via an ester bond. The tailored design of bioactive materials based on cellulose or paper is still a challenging task. It requires detailed knowledge of the structure and interaction of the biofunctionalization with the carrier material at the nanoscale. In this work, the small peptide sequence Acetyl-Pro-Ala-Phe-Gly-OH (peptide 1) that can serve as a model for biofunctionalization is synthesized via solid-phase peptide synthesis, purified, and characterized by high-performance liquid chromatography (HPLC) and mass spectrometry (MS). The as-obtained peptide is bound to microcrystalline cellulose (MCC) via a wet chemical approach. Quantification of the peptide on the MCC carrier is performed by replacing l-proline (Pro) in the peptide sequence by 4-fluoro-l-proline (Pro(19F)) (peptide 2) and applying 19F magic angle spinning nuclear magnetic resonance (MAS NMR). Detailed characterization of the model system is provided by using 1H → 13C cross-polarization magic angle spinning (CP MAS NMR) combined with dynamic nuclear polarization (DNP) to enhance sensitivity. Analysis of the binding of the peptide on MCC necessitates the replacement of l-glycine (Gly) in the sequence by 13C-labeled l-glycine (Gly(13C)) (peptide 3). DNP-enhanced 13C–13C correlation experiments carried out with dipolar assisted rotational resonance (DARR) are then used to analyze the proximity between the model peptide and the MCC carrier. The strength of the dipolar coupling is estimated from the DNP-enhanced 1H → 13C CP MAS double-quantum rotational resonance (DQrotres) experiment. The obtained dipolar coupling between the 13C═O carbon of peptide 3 and the C6 carbon of the cellulose is equal to a carbon–carbon distance of about two C–O bond lengths, which strongly suggests the binding of significant amounts of the peptide on MCC via an ester bond.

The Rapid Mechanochemical Synthesis of Microporous Covalent Triazine Networks: Elucidating the Role of Chlorinated Linkers by a Solvent-Free Approach - Krusenbaum, Annika; Kraus, Fabien Joel Leon; Hutsch, Stefanie; Grätz, Sven; Höfler, Mark Valentin; Gutmann, Torsten; Borchardt, Lars (Advanced Sustainable Systems)
Abstract The mechanochemical synthesis of porous covalent triazine networks (CTNs), exhibiting theoretically ideal C/N ratios and high specific surface areas, is presented. Employing this solvent-free approach allows to minimize the ecological impact of the synthesis by bypassing hazardous wastes, while simultaneously observing the reactions between the individual starting materials separately for the first time. Especially the role of dichloromethane needs to be reconsidered, functioning as a linker between the nitrogen-containing node cyanuric chloride and the aromatic monomer 1,3,5-triphenylbenzene, as proven by X-ray photoelectron spectroscopy and 1H â†’ 13C Cross-Polarization magic-angle-spinning nuclear magnetic resonance spectroscopy. This results in a drastic enhancement of the reaction rate, reducing the synthesis time down to 1 minute. Additionally, this linkage over a C1 bridge enables the incorporation of nitrogen into already synthesized polymers by post polymerization functionalization. The variation of the synthesis building blocks, namely the linker, node, and monomer, results in a variety of nitrogen-containing polymers with specific surface areas of up to 1500 m2 gâˆ’1. Therefore, the presented approach is capable to target the synthesis of various CTNs with a minimal use of chlorinated linker, rendering the concept as a sustainable alternative to the classical solution-based synthesis.